KAJIAN KONSEP TAMAN ISLAM BERDASARKAN AL-QURAN DAN HADIS - Miftahul Jannah; Wahju Qamara Mugnisjah; Andi Gunawan (El Harakah, 2016)
Islam is a religion with a comprehensive concept (syumuliyyah), included in planning and designing a garden. Until now, there have been various studies about Islamic garden, but in general, it doesn’t refers to the Islamic law itself. This study wants to make a brief comparison between the concept of Islamic garden that emerge in Islamic glory period and the concept that based on Islamic law. The data collection are using study literature methods from two major literatures in Islam (Quran and hadith), and other literatures (books, journals, and research reports) that are related. As a results, it is revealed that the concept of Islamic garden nowadays still doesn’t refer to the primary sources of Islamic law, and it is more restrictive. It should be emphasized that basically the planning and designing concept of Islamic garden could be more free, adjusted to the location, and the needs of garden users.